Some trouble with cows : making sense of social conflict - Roy, Beth. (Berkeley : University of California Press, 1994)
Fascinating in its combination of personal stories and analytical insights, Some Trouble with Cows will help students of conflict understand how a seemingly irrational and archaic riot becomes a means for renegotiating the distribution of power and rights in a small community. Using first-person accounts of Hindus and Muslims in a remote Bangladeshi village, Beth Roy evocatively describes and analyzes a large-scale riot that profoundly altered life in the area in the 1950s. She provides a rare glimpse into the hearts and minds of the participants and their families, while touching on a range of.
Cover Page; Title Page; Copyright Page; Table of Contents; Acknowledgments; Maps; The Cast of Characters; Introduction; Part One: Making Trouble; Chapter 1. The Quarrel; Chapter 2. The Decision; Chapter 3. The Riot; Chapter 4. Intervention and Punishment; Chapter 5. Reconciliation and Thereafter; Part Two: Making Sense; Chapter 6. Lessons of Panipur; Chapter 7. Self and Decision; Chapter 8. Community and Identity; Chapter 9. History and Ideology; Chapter 10. Bringing History Home; Appendix A: Chronology; Appendix B: Land Relations in Panipur; Notes; Names and Terms; Bibliography; Index.
Includes bibliographical references (pages 217-228) and index.
Print version record.
In English.
JSTOR
Keywords: Communalism -- Bangladesh; Hindus -- Bangladesh; Muslims -- Bangladesh; Communalisme -- Bangladesh; Hindous -- Bangladesh; Musulmans -- Bangladesh; SOCIAL SCIENCE -- Violence in Society; RELIGION -- Hinduism -- General; Communalism; Hindus; Muslims; Bangladesh; Religious groups; Bangladesh; Electronic books